Establishment of Quality Evaluation Method for Yinqiao Powder: A Herbal Formula against COVID-19 in China. (25th November 2022) - Zhang, Huimin; Xu, Lin; Song, Jian; Zhang, Aijun; Zhang, Xiao; Li, Qingjun; Qu, Xinyan; Wang, Ping
Abstract : Yinqiao powder, with significant anti‐inflammatory and antiviral effects, is a classical formula for the treatment of febrile diseases in China. During the SARS period in 2003, Yinqiao powder showed a good antipyretic effect. It also plays a major role in the treatment for COVID-19 in China. Although there are many studies on the chemical compositions and pharmacological effects of Yinqiao powder, there are few studies on the quality standard system of it. In our study, a systematic quality evaluation method of Yinqiao powder combining HPLC fingerprint with quantitative analysis of multi-components by single marker (QAMS) based on network pharmacology and UPLC-Q-Exactive-Orbitrap-MS was established for the first time. In the UPLC-Q-Exactive-Orbitrap-MS experiment, a total of 53 compounds were identified in the extract solution of Yinqiao powder. In addition, 33 blood components were characterized, 23 of which were prototypes. The results of network pharmacology analysis showed that Yinqiao powder may inhibit inflammatory responses by suppressing IL-6, CXCL2, TNF α, NF- κ B, etc., in the treatment of COVID-19. The HPLC fingerprint analysis of Yinqiao powder was conducted at 237 nm and 29 characteristic peaks were matched, 11 of which were identified. Forsythoside A was selected as the internal standard reference and double-wavelength (237 nm and 327 nm) was established in QAMS experiment. The repeatability was well under different conditions, and the results measured by QAMS were consisted with that of the external standard method (ESM), indicating that the QAMS method was reliable and accurate. The quality evaluation method of Yinqiao powder would be helpful to evaluate the intrinsic quality of Yinqiao powder more comprehensively, which is conducive to improve the quality standard of Yinqiao powder and provide a beneficial guarantee for the clinical treatment of COVID-19.